The Indonesian Goverment's Strategy in Maintaining and Increasing UAE Investment Interset in 2015-2022 - Mukin, Sahmun Karihan; Putra, Alde Mulia (UNIDA GONTOR, 2024)
In maintaining the interest of UAE investment in Indonesia, the government and the President made various efforts to maintain this trust. Before heading to the main discussion, namely maintaining investment interest, President Jokowi and the government visited the UAE from 2015 to 2022. President Jokowi, chose the UAE as a visited country for various strong reasons in it which include the wealth owned by the UAE state and the activity of the UAE state in the international world in terms of investment. Visit after visit made by President Jokowi created good results and created various agreements, one of which was IUEA-CEPA by using IKN as the main attraction of the Indonesian state in the eyes of investors. After successfully conducting economic diplomacy in the UAE, President Jokowi and the government know the shortcomings of the Indonesian state which can be an obstacle to the course of investment in Indonesia. In order to create a good investment climate, the government carries out various strategies and policies related to investment which can reduce various problems. These problems include; corruption, bureaucracy, and convoluted regulations. With various strategies that are considered successful, it has a major impact on the economic progress of the Indonesian state both in terms of infrastructure, economic development, and people's welfare (job creation). Looking at the lens of Islam, the strategies and efforts made by President Jokowi and the Indonesian government are considered as fair, and honest attitudes as well as good attitudes in maintaining trust. Please note, this research is quantitative by using theory as the basis for discussion. The theories used are theories relevant to this research including; Economic Diplomacy, and Stephen D Cohen's FDI theory. The data obtained in this study uses various sources including, documents, books, websites, social media (You tube), and statistical data obtained from the official website of the data owner (BUMN, BKPM, WorldBank, UNCTAD, and others) In maintaining the interest of UAE investment in Indonesia, the government and the President made various efforts to maintain this trust. Before heading to the main discussion, namely maintaining investment interest, President Jokowi and the government visited the UAE from 2015 to 2022. President Jokowi, chose the UAE as a visited country for various strong reasons in it which include the wealth owned by the UAE state and the activity of the UAE state in the international world in terms of investment. Visit after visit made by President Jokowi created good results and created various agreements, one of which was IUEA-CEPA by using IKN as the main attraction of the Indonesian state in the eyes of investors. After successfully conducting economic diplomacy in the UAE, President Jokowi and the government know the shortcomings of the Indonesian state which can be an obstacle to the course of investment in Indonesia. In order to create a good investment climate, the government carries out various strategies and policies related to investment which can reduce various problems. These problems include; corruption, bureaucracy, and convoluted regulations. With various strategies that are considered successful, it has a major impact on the economic progress of the Indonesian state both in terms of infrastructure, economic development, and people's welfare (job creation). Looking at the lens of Islam, the strategies and efforts made by President Jokowi and the Indonesian government are considered as fair, and honest attitudes as well as good attitudes in maintaining trust. Please note, this research is quantitative by using theory as the basis for discussion. The theories used are theories relevant to this research including; Economic Diplomacy, and Stephen D Cohen's FDI theory. The data obtained in this study uses various sources including, documents, books, websites, social media (You tube), and statistical data obtained from the official website of the data owner (BUMN, BKPM, WorldBank, UNCTAD, and others)